Beyond Demographic Dividends - Cai, Fang (Series on Chinese economics research, 2014)
This book presents empirical observations and theoretical thinking of the fundamental changes in the Chinese economy. It starts with a warning of the arrival of the Lewis turning point, which is empirically proven by disappearance of surplus labor force and a rapid increase in wages of unskilled workers. It further reveals that China's rapid population-aging trend is diminishing the demographic dividend that has kept China's economic growth rate high. Subsequently, it touches upon employment challenges that arise after reaching the Lewis turning point, further propelling urbanization, a balanced regional development, and so on. Finally, it introduces middle-income trap which is one of the biggest challenges China is facing, followed by recommendation of policies for the Chinese government to tackle the challenges ahead. This book should be of great interest to graduates, undergraduates, researchers and specialists who follow closely the economic development and demographic transition of China, the world's most populous country.